I’adah Of Friday Prayer With Zuhr Prayer In The Perspective Of Fiqh Shafi'iyyah: (Case Study in Al-Amin Mosque, Meurah Village, Samalanga District, Bireuen Regency) - Mukhtar, Safrizal (Jurnal Al-Fikrah, 2024)
This research describes the determination of the legal I’adah for Friday prayers and noon prayers in Syafiiyah fiqh. The Friday prayer prayer has become a habit carried out by the congregation of the Al-Amin Meurah Samalanga mosque. However, there are also mosques around Samalanga that do not perform Friday prayers. This research analyzes the factors that cause Friday prayers at the Al-Amin Mesjid Meurah Samalanga. This research is field research using qualitative descriptive research methods. The author uses an empirical or sociological (empirical or sociological) approach. The conclusion of this research is that the Friday prayers with noon prayer are carried out by the congregation at the Al-Amin Meurah Mosque, Samalanga sub-district, Bireun Regency because they believe that there are less than 40 members of the Friday congregation because there are still some people who do not come to the mosque but choose to to pray at other mosques around Samalanga.